Motion Planning of Compliant Parallel Robot - Tian Hao; Yu Yueqing (Jixie chuandong)
The research on motion planning of the parallel robot with compliant joints is carried out.According to the characteristics of compliant joint,the system analysis model is built.The dynamics equation is obtained based on Lagrange method.To guarantee the smooth running of the system and suppress the rate of speed of inertia force,the trapezoidal and S-curve velocity planning method are used for motion planning.The motion planning algorithms of linear and circular trajectories are given.The simulation results show that the motion planning method is effective.